Morgan Stanley : the events of September 11, 2001 (B) - Ulto, Stephanie; Strmiska, Dorinda; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
When two airplanes struck the World Trade Center on September 11, 2001, more than 3,000 Morgan Stanley employees sprang into action. Following an earlier terrorist attack on the Center in 1993, the company developed an emergency evacuation plan to ensure employees could safely and quickly exit the building. With all the chaos following the attacks, CEO Phil Purcell had difficulty in determining if all of the companys employees had made it out. News was also traveling around the world that Morgan Stanley was completely destroyed from the bombing. Purcell must quickly determine how many employees survived and how to inform the world that Morgan Stanley was still in business.
Originally published: Ulto, S., Strmiska, D., & ORourke, J. S. (2002). Morgan Stanley: The events of September 11, 2001 (B). 02-02 (B). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Morgan Stanley (Firm); Financial services industry -- United States -- Case studies; Investment banking -- United States -- Case studies; Emergency management -- United States -- Case studies; September 11 Terrorist Attacks, 2001 -- Case studies